Sejarah Dan Dinamika Pembaharuan Lembaga Pendidikan Islam Di Nusantara : Surau, Pesantren Dan Madrasah - Muhammad Aldian Syah; Muhammad Zalnur; Fauza Masyudi (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this study is to examine the history and dynamics of Islamic educational institutions in the archipelago, namely surau, pesantren, and madrasah. In the process of education, educational institutions play a very important role as they function as places of learning. The existence of educational institutions facilitates the process of acquiring knowledge. The Islamic educational institutions in the archipelago include surau, pesantren, and madrasah. Surau and pesantren are classical Islamic educational institutions and are also referred to as authentic (indigenous) Islamic educational institutions. The reason surau and pesantren are considered authentic educational institutions is that they originated from the community and their models were not influenced by external models, but instead, they are characteristic of the archipelago. This research uses the library research method, where the sources of this study are books and previous articles related to Islamic educational institutions in the archipelago. The findings of this study show that the arrival of Islam in the archipelago cannot be separated from the influence of education. The beginnings of Islamic education started when Islam entered the archipelago in a simple form. Education became a top priority for the Muslim community in the archipelago since that time, marking the beginning of the development of Islam.